2010
DOI: 10.1111/j.1365-2567.2010.03352.x
|View full text |Cite
|
Sign up to set email alerts
|

The αE(CD103)β7 integrin interacts with oral and skin keratinocytes in an E-cadherin-independent manner*

Abstract: SummaryThe integrin aE(CD103)b7 (aEb7) is expressed by intraepithelial lymphocytes, dendritic cells and regulatory T cells. It plays an important role in the mucosal immune system by retaining lymphocytes within the epithelium and is involved in graft rejection, immunity against tumours and the generation of gut-homing effector cells. In gut and breast, the ligand for aEb7 is E-cadherin but in human oral mucosa and skin, there is evidence that lymphocytes use an alternative, unknown, ligand. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…We and others have observed that leukocytes can penetrate and traverse the SC following placement in the vaginal lumen (apical-to-basal infiltration), suggesting a mechanism for cell-associated HIV transmission via infected cells deposited in semen 3133 . Leukocytes may freely move through this cell layer because the epithelial cells lack e-cadherin 16 and possibly other adhesive molecules that retain and integrate immune cells in mucosal epithelia 34,35 . It is currently unknown to what extent leukocytes actively perform immunosurveillance of this cell layer.…”
Section: The Vaginal Stratum Corneum Microenvironmentmentioning
confidence: 99%
“…We and others have observed that leukocytes can penetrate and traverse the SC following placement in the vaginal lumen (apical-to-basal infiltration), suggesting a mechanism for cell-associated HIV transmission via infected cells deposited in semen 3133 . Leukocytes may freely move through this cell layer because the epithelial cells lack e-cadherin 16 and possibly other adhesive molecules that retain and integrate immune cells in mucosal epithelia 34,35 . It is currently unknown to what extent leukocytes actively perform immunosurveillance of this cell layer.…”
Section: The Vaginal Stratum Corneum Microenvironmentmentioning
confidence: 99%
“…The α E β 7 integrin has been associated with lung, gut, and skin homing, whereas the α 4 β 7 integrin has been associated with gut homing (21). Skinhoming α E + β 7 + T cells also express CLA (38). We therefore investigated the expression of the α E β 7 integrin in the whole CD3 + T cell compartment, in the CD3 + CLA + T cell compartment ( Figure 3D, Supplemental Figure 7, C and F, and Supplemental Figure 8D), and in the various naive and memory T cell compartments of the patients' PBMCs (Supplemental Figure 9, C and D).…”
Section: Identification Of a Nonsense Mutation In The Rhoh Gene We Imentioning
confidence: 99%
“…In addition to E-cadherin, aEb7 integrin is known to have two other ligands. One is a ligand expressed on microvascular endothelial cells (24), whereas the other is expressed on oral and skin keratinocytes (25). Details of these two ligands are yet to be clarified.…”
mentioning
confidence: 99%